In the shadow of the mountains - Naylor, Helen (Cambridge English readers. Level 5, 1999)
Clare Newton, a journalist, travels to Switzerland to bring home the body of her grandfather, which has appeared from the bottom of a glacier 74 years after a climbing accident. Or was it an accident? Clare finds more about her family's past than she expected and reaches decisions about her personal and professional life.